LANGUAGE STYLE ANALYSIS IN THE MAIN CHARACTER UTTERANCES IN CINDERELLA (2021) MOVIE - Aprilia, Anissa Dwi; Arifin, M. Bahri; Ariani, Setya (Fakultas Ilmu Budaya Universitas Mulawarman, 2024)
This research aims to find language style using Joos’ theory and to analyze function of language style using Jacobson’s theory in Cinderella (2021) movie used by the main character in the movie. This research used the qualitative method. The data were generated from the movie and movie scripts in the form of phrase and sentence expressed by the main character. The result of the study showed that there were 105 data that contained language style and function of language style in the movie. There were four types of language style such as formal style, consultative style, casual style, and intimate style. Casual style is the most dominant type of language style was found in this research because Cinderella as the main character often used this style and it fitted to the situations that she had frequently in daily conversations than other style in the movie. There were five types of function of language style such as expressive function, directive function, referential function, metalinguistic function, and phatic function. Expressive function is the most dominant type of function of language style was found in this research because the main character often expressed her feeling and her thought in her utterances in the movie.